Health and wellbeing of adolescent girls in a hilly district of Himachal Pradesh: a cross sectional study using low cost interventions - Jindal, Nidhi; Jindal, Nipun; Badrel, Ajay (International Journal Of Community Medicine And Public Health, 2020)
Background: Adolescence is a phase when major physical, psychological, emotional and psychosocial changes take place and it is imperative to meet the unmet needs of this age group especially the girls for optimizing their future contribution during adulthood. The objective of this study was to assess the indicators of the well being and health of school going adolescent girls in District Shimla of Himachal Pradesh and evaluating the effectiveness of a local developed questionnaire for assessment. Methods: A symptomatology based questionnaire was employed for screening the adolescent girls for anaemia, calcium and vitamin D deficiency, worm infestation, menstrual problems, reproductive tract problems and BMI was used for their overall nourishment status. The questionnaire was administered by trained health care workers. Results: The prevalence of anaemia came out to be 21.54% while 12.37% and 7.51% girls had signs of calcium deficiency and worm infestation respectively. 9.38% girls had menstrual problems while 1.9% had sexual health problems. 15.32% girls came out to be malnourished in the survey. Conclusions: Appropriate interventions need to be formulated properly taking into consideration the problem statements and executed well for improvement of health concerns of adolescent girls. If the resources are constrained, low cost interventions can be deployed locally in the communities depending upon the problems encountered to achieve optimum results.